Lifestyle Factors Impact on Breath Hydrogen and Gastrointestinal Symptoms After Consumption of Gluten and Inulin in Adults With and Without IBS. (14th June 2022) - Evenson, Alexa; Windsperger, Austin; Metelmann, Linnea; Meyer-Iverson, Decorah; Johnson, Grace; Anderson, Lydia; Rooney, Elissa; Stovern, Shelby; Zwack, Codi; Brewer, Katie
Abstract: Objectives: To investigate the relationships and differences in lifestyle factors including anxiety level, physical activity, diet, and sleep on breath hydrogen and gastrointestinal symptoms in individuals with and without IBS after consumption of gluten and Inulin. Methods: A double-blind, randomized, controlled crossover design was conducted with 24 non-IBS and 14 IBS participants. Fasted participants consumed a control low FODMAP smoothie and treatment smoothies that consisted of the low FODMAP base and gluten (5g) or inulin (5g). Breath hydrogen was measured at Baseline, 1, 2, and 3 hours. GI symptoms were measured at baseline, .5, 1, 1.5, 2, 3, 12, and 24 hours. The STICSA and IPAQ-SF measured state and trait anxiety and physical activity (minutes and METS) during each treatment. The NCI Dietary Screener and PSQI surveys measured dietary intake and sleep at one time point as they assess behavior for the past 30 days. Independent t-tests were used to analyze dietary intake and sleep variables between the non-IBS and IBS groups. Spearman rho and multiple repeated ANOVA and Simple-Effect tests were used to analyze variables based on treatments. Significance was set at p  < .05. Results: Dietary variables, physical activity minutes and METS, and sleep did not correlate to breath hydrogen or GI symptoms for any treatment (p > .05). There were no differences between non-IBS and IBS groups in any diet variable including fruits, vegetables, fiber, dairy, added sugar, whole grains, or sleep (p > .05). There were no differences in state-somatic, state-cognitive, state-total, trait-somatic, trait-cognitive, or trait-total in either treatment or non-IBS and IBS groups (p > .05), except for the inulin treatment saw a difference in state-cognitive between non-IBS and IBS groups (MD = 4.071; p = .043) with the IBS group having more state cognitive anxiety during the inulin treatment. However, state-cognitive anxiety was not related to breath hydrogen or GI symptoms for the inulin treatment (p > .05). Conclusions: In this sample of individuals with and without IBS, lifestyle factors such as dietary intake, physical activity, anxiety, and sleep did not differ significantly between groups nor was related to breath hydrogen levels or GI symptoms. Lifestyle factors may not play a large role in the development of GI symptoms. Funding Sources: CSBSJU Undergraduate Research Grant.